Seismicity of the Territory of Bulgaria and Adjacent Lands Based on NOTSSI Data for 2023 - Emil Oynakov; Mariya Popova (GeoStudies, 2024)
The present study comprehensively analyzes seismic events recorded by the National Operative Telemetric System for Seismological Information (NOTSSI) in 2023. Seismic data are collected in real-time by 26 Bulgarian stations, supplemented by numerous stations from neighboring countries, enhancing the precision of hypocentral location determinations. The main kinematic parameters and the magnitude of the earthquakes are estimated utilizing an adaptation of the product HYPO’71. In the practice of NOTSSI, two types of magnitude estimates are used. Magnitude MP is determined by measuring the maximum amplitude of the P wave. The seismic moment magnitude MW is estimated from the seismic moment M0 - a quantity that combines the rupture area and the residual displacement along the fault with the strength properties of the medium (shear modulus µ). The present study transforms MP, into the more reliable and widely used magnitude scale MW.MW allows for homogenizing the magnitude estimates in the available seismological information and creating a homogenized catalog. The energetically homogenized catalog ensures compatibility of the input seismological information and a reliable assessment of the energetic distribution of earthquakes. The year 2023 was remarkable for the two devastating earthquakes, magnitudes M7.8 and M7.5, that occurred in Eastern Turkey on February 6th, followed by more than 40 000 aftershocks. They caused human losses and enormous material damage. Although they were more than 1500 km from the territory of Bulgaria, the main shocks were partially felt on the high floors of some buildings.The earthquakes analyzed in Bulgaria and its surroundings in 2023 were primarily low-magnitude events with uneven spatiotemporal distribution. The hypocenters’ depth distribution was in the upper levels of the earth’s crust. The largest number of events were registered in the Rilo-Rhodope seismic area, which covers the Struma and Rhodope seismic zones. The highest concentration of seismic events is observed again in the Struma seismic zone. In the Srednogorie region, along the Maritsa River valley, on June 7, 2023, occurred the strongest earthquake for 2023. It had a magnitude of 4.8 and an intensity of 6.5 in the epicentral area.Looking at the overall picture of earthquakes in Bulgaria in 2023, we should also note the weak seismic events in the Burgas and Strandzha regions in Southeastern Bulgaria and the region of Northwestern Bulgaria.For the last five years, 2023 has been characterized by the highest seismicity, as measured by the number of registered events (68 with MW>3) and the highest magnitude (MW4.8).